The management of refractory generalised convulsive and complex partial status epilepticus in three European countries: a survey among epileptologists and critical care neurologists. Issue 8 (21st July 2003) - Holtkamp, M; Masuhr, F; Harms, L; Einhäupl, K M; Meierkord, H; Buchheim, K
Abstract : Objective: To survey the current clinical treatment of refractory status epilepticus and to identify steps in its management which may need further investigation. Methods: Epileptologists and critical care neurologists were surveyed using a standardised postal questionnaire. Results: Sixty three of 91 participants (69%) returned the questionnaires. Two thirds of the respondents applied another non-anaesthetising anticonvulsant after failure of first line drugs. General anaesthesia for ongoing complex partial status epilepticus (CPSE) was part of the therapeutic regimen of 75% of the interviewees. A non-barbiturate as general anaesthetic of first choice was used by 42%. Up to 70% titrated the anaesthetic to achieve a burst suppression pattern in the electroencephalogram, indicating deep sedation, and 94% reduce anaesthesia within 48 hours. Conclusions: The management of refractory status epilepticus is heterogeneous in many aspects, even among clinicians who are most familiar with this severe condition. Randomised trials are needed to compare the efficacy, side effects, optimal duration, and depth of general anaesthesia.